2016
DOI: 10.1038/leu.2016.66
|View full text |Cite
|
Sign up to set email alerts
|

The role of Fas-associated phosphatase 1 in leukemia stem cell persistence during tyrosine kinase inhibitor treatment of chronic myeloid leukemia

Abstract: Chronic myeloid leukemia (CML) is characterized by expression of Bcr-abl, a tyrosine kinase oncogene. Clinical outcomes in CML were revolutionized by development of Bcr-abl-targeted tyrosine kinase inhibitors (TKIs), but CML is not cured by these agents. CML leukemia stem cells (LSCs) are relatively TKI insensitive and persist even in remission. LSC persistence results in relapse upon TKI discontinuation, or drug resistance or blast crisis (BC) during prolonged treatment. We hypothesize that increased expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 40 publications
1
28
0
Order By: Relevance
“…Exaggerated granulocytosis is observed during infection in chronic myeloid leukemia (CML) and chronic myelomonocytic leukemia (CMMoL), but the role of emergency granulopoiesis in these diseases is unknown. This may be a useful area of investigation, since CML and CMMoL are characterized by decreased activity of Icsbp; a key activator of FANCC and FANCF transcription (43–45). …”
Section: Discussionmentioning
confidence: 99%
“…Exaggerated granulocytosis is observed during infection in chronic myeloid leukemia (CML) and chronic myelomonocytic leukemia (CMMoL), but the role of emergency granulopoiesis in these diseases is unknown. This may be a useful area of investigation, since CML and CMMoL are characterized by decreased activity of Icsbp; a key activator of FANCC and FANCF transcription (43–45). …”
Section: Discussionmentioning
confidence: 99%
“…We investigated Stat3 for activity on the human IRF8 promoter, but did not see an effect of either overexpression or knockdown of this transcription factor (data not shown). Xiap1 is a Calpain substrate of potential interest, since our previous studies identified regulation of Fas-induced apoptosis as a role for Icsbp during myelopoiesis and in leukemogenesis [14, 15, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…For some experiments, cells were transduced with retroviral vectors to express p210 Bcr-abl (in MiGR1 vector), DN-Gas2 (in MSCVpuro vector), or DN-Shp2 (in MSCVneo vector). Replication incompetent retroviral vectors were generated using the Ecopack packaging plasmid, as described [23]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This induced Fas-resistance and enhanced transcription of βcatenin target genes, including BIRC5 (encoding Survivin). In a murine model of CML, we determine treatment with Imatinib (IM; a TKI inhibitor) plus a Fap1-blocking peptide prevented chronic phase (CP) relapse or blast crisis (BC) progression, although IM alone did not [12]. And, mice treated with IM plus Fap1-blocking peptide sustained remission after therapy discontinuation, although 60% of mice treated with IM alone relapsed.…”
Section: Introductionmentioning
confidence: 99%